Wind stress and fluxes of sensible and latent heat over the Arabian Sea during ISMEX-I973 - PANT, M. C. (MAUSAM, 1977)
During the Indo-Soviet Monsoon Experiment (ISMEX) in the year 1973, four Russian research vessels Vocikov, Okean, Shokaliasky and Priliv remained stationary at locations near 00.1 oN, 49 .6°E; 00 .1 oN. 60.0°E; 10.0°N. 60.0°E and 18 .O°N, 67.0°E respectively from 28 June to 2 July 1973. Hourly surface observations were taken on board the ships during this period. From these observations hourly values of shearing stress of wind at the surface and vertical fluxes of sensible and latent heat at the air-sea interface are computed by using the bulk aerodynamic formulae. A variable drag coefficient with wind speed is used as suggested by Deacon and Webb (1962). Hourly values of the Richardson number (Ri) for the four locations are also computed. It is found that the surface layers at locations near 00 .1°N, 49.6oE; 10.0°N, 60.0°E and 18.0°N, 67.0°E show near neutral stability conditions. The wind stress values are comparatively smaller at the equatorial locations than those at the northern ones. A marked increase in the wind stress occurs in association with a surge in the monsoon current. The sensible heat flux shows a well defined diurnal variation which is in close conformity with the diurnal variations of the air sea temperature difference. Maximum positive flux occurs around mid-night or dawn hours and minimum around mid-day or afternoon hours. An 'actual reversal of direction of the sensible heat flux is found to occur at noon hours particularly at the northern locations near 10.0°N, 60 .O°E and 18.0°N. 67.0°E during the period of study. The latent heat flux remains positive at all times of the day and shows a relative decrease or increase with a decreas3 or increase in the wind speed. While the sensible heat flux shows a marked increase during disturbed weather period, the latent heat flux shows a decrease during the same period.